2017
DOI: 10.1097/med.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta: diagnosis and treatment

Abstract: Despite advances in the diagnosis and treatment of osteogenesis imperfecta, more research is needed. Bisphosphonate treatment decreases long-bone fracture rates, but such fractures are still frequent. New antiresorptive and anabolic agents are being investigated but efficacy and safety of these drugs, especially in children, need to be better established before they can be used in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…This gene encodes the pro-alpha1 chains of type I collagen (Zhang et al, 2018b;Zhang et al, 2018a, p. 1). COL1A1 is often found in connective tissues (e.g., bone and tendon) and thus its mutation is most closely associated with osteogenic diseases, specifically osteogenesis imperfecta (Palomo, Vilaça & Lazaretti-Castro, 2017). Dysregulation of COL1A1 has been identified in several different cancers including breast (Liu et al, 2018, p. 1) protocol (see Methods for details).…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes the pro-alpha1 chains of type I collagen (Zhang et al, 2018b;Zhang et al, 2018a, p. 1). COL1A1 is often found in connective tissues (e.g., bone and tendon) and thus its mutation is most closely associated with osteogenic diseases, specifically osteogenesis imperfecta (Palomo, Vilaça & Lazaretti-Castro, 2017). Dysregulation of COL1A1 has been identified in several different cancers including breast (Liu et al, 2018, p. 1) protocol (see Methods for details).…”
Section: Discussionmentioning
confidence: 99%
“…To control pediatric ODs, N-BPs were first used only in the 90s, with the application of pamidronate to treat osteogenesis imperfecta (OI) (Eghbali-Fatourechi, 2014). Nowadays, N-BPs are considered the first line in the management of most pediatric ODs (Baroncelli & Bertelloni, 2014;Eghbali-Fatourechi, 2014;Palomo, Vilaça, & Lazaretti-Castro, 2017;Soares et al, 2016) and are also indicated for other conditions, such as the recovery of bone mass and the reduction of fracture rates in bone disorders associated with immobilization (Baroncelli & Bertelloni, 2014;Eghbali-Fatourechi, 2014). The main N-BPs prescribed in pediatric patients are alendronate, pamidronate, and zoledronate (Baroncelli & Bertelloni, 2014;Eghbali-Fatourechi, 2014;Muderis, 2007) the last one being specifically used in the treatment of pediatric bone malignancies (Eghbali-Fatourechi, 2014).…”
Section: Main Clinical Applicationsmentioning
confidence: 99%
“…there are no standardized protocols for each condition (use and duration of therapy); their side effects in axial-appendicular and craniofacial skeletal growth and their impact in adulthood have not been extensively evaluated (Baroncelli & Bertelloni, 2014;Palomo et al, 2017;Soares et al, 2016); and the long-term safety of the drugs in childhood is unclear because of the pediatric physiological characteristics of bone remodeling (Baroncelli & Bertelloni, 2014;Palomo et al, 2017).…”
Section: Main Clinical Applicationsmentioning
confidence: 99%
“…The repeatedly revised classification of OI is based on the assessment of phenotype and determination of genotype [ 4 ]. At present, mainly four [ 16 ], [ 54 ] or five [ 4 ] types are distinguished. However, much more subtypes are classified in clinical research through improved genetic analyses of affected individuals [ 4 ], [ 16 ].…”
Section: Discussionmentioning
confidence: 99%